The Modeling of Comprehensive Evaluation System of College Teachers' Professional Quality Based on Deep Learning. (16th September 2022) - Yang, Xiaoying
Abstract : As a significant part of national education, the quality and ability of college teachers determine the level and height of the connotation growth of higher education in China. With the advent of the 21st century, society has entered a new stage of rapid development of knowledge economy. Promoting the coordinated and sustainable development of human and natural society has become an important topic of social research. The great rejuvenation of the nation and the progress of society all show the demand for high-quality talents. As an important base for cultivating high-quality talents, colleges and universities must shoulder the mission entrusted by the state. The cultivation of high-quality talents requires not only scientific educational guiding ideology but also a set of student comprehensive quality evaluation index system to evaluate students' comprehensive quality. Colleges and universities must reform the comprehensive evaluation system of teachers' quality, clarify the objectives of the comprehensive evaluation of teachers' quality, reasonably set the evaluation content, use the correct evaluation means, mobilize the enthusiasm of teachers, promote the construction of teachers' team, and improve the competitiveness of colleges and universities according to the laws of education and teaching and the professional characteristics of teachers. This paper adopts the method of deep learning to evaluate the comprehensive quality of teachers, and the corresponding complete evaluation system of teachers' comprehensive quality is gradually formed. Judging from the actual situation of the reasonable evaluation of college teachers, the evaluation of teachers' psychological quality, teaching curriculum quality, and ideological and moral quality with the help of this system can provide a good guarantee for the continuous optimization and improvement of teachers. At the same time, it can play an important and positive role in the continuous improvement of teachers and the innovation and development of classroom teaching. Based on this, it is necessary to discuss the construction of the comprehensive quality evaluation system of college teachers.